Desain Pembelajaran Student's Conceptual Construction Guider Berdasarkan Kesulitan Mahasiswa Calon Guru Fisika pada Konsep Gerak Parabola - Duden Saepuzaman; Saeful Karim (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
Abstract This research is motivated finding of the student difficulties in projectile motion. In general, the difficulties students in understanding the concept of projectile motion as follows. First, draw the vector component’s in the direction x (horizontal) and y (vertical). Second, distinguish the velocity vector’s , the vector component of velocity, the velocity vector component in the x and y directions. Third, too focus on formula’s for half a projectile trajectory, maximum height, maximum distance. Fourth, always assumed final velocity moving object projectile when it hits the ground is always zero. Fifth, the velocity to zero at the top (only the speed in the vertical direction is zero). Sixth, the acceleration is owned by the object in the x and y directions. Seventh, found some students use the law of sines cosines rule’s on the determination of the distance /height (although the determination of the distance / high based on the speed information). In Prediction, the process of learning that takes less facilitate the development of thinking ability of students to build its own concept (constructivism). This research aims to create a lesson plan called Student's Conceptual Construction Guider. The method used is descriptive analysis method. Conceptual understanding of students are evaluated through tests shaped conceptual description. The results showed that the learning Student's Conceptual Construction Guider can facilitate the development of thinking ability of students to build its own concept in understanding the concept of a projectile motion Keywords: Student's Conceptual Construction Guides, student difficulties, Projectile Motion Abstrak Penelitian ini dilatarbelakangi karena ditemukannya kesulitan-kesulitan mahsiswa dalam mempelajari konsep gerak parabola. Secara umum, kesulitan-kesulitan mahasiswa dalam memahami konsep gerak parabola sebagai berikut. Pertama, menggambarkan vektor komponen dalam arah x (horizontal) dan y (vertikal). Kedua, membedakan vektor kecepatan, vektor komponen kecepatan, komponen vektor kecepatan dalam arah x dan y. Ketiga, terfokus pada hapalan rumus waktu yang ditempuh peluru untuk lintasan setengah parabola, tinggi maksimum,jarak terjauh maksimum. Keempat, selalu beranggapan kecepatan akhir benda yang bergerak parabola ketika menyentuh tanah selalu nol. Kelima, kecepatan benda nol di puncak (padahal hanya kecepatan dalam arah vertikal yang nol). Keenam, percepatan dimiliki oleh benda dalam arah x maupun y. Ketujuh, ditemukan beberapa mahasiswa menggunakan aturan sinus cosinus segitiga pada penentuan jarak/ ketinggian dan sebaliknya (padahal penentuan jarak/ketinggian berdasarkan informasi kecepatan). Diduga kuat, proses pembelajaran yang terjadi kurang memfasilitasi pengembangan kemampuan berpikir mahasiswa untuk membangun konsepnya sendiri (konstruktivisme). Penelitian ini bertujuan untuk membuat sebuah rancangan pembelajaran yang disebut Student’s Conceptual Construction Guider. Metode yang digunakan adalah metode analisis deskriftif. Pemahaman konseptual mahasiswa dievaluasi melalui tes konseptual yang berbentuk uraian. Hasil penelitian menunjukkan bahwa pembelajaran Student’s Conceptual Construction Guider dapat memfasilitasi memfasilitasi pengembangan kemampuan berpikir mahasiswa untuk membangun konsepnya sendiri dalam memahami konsep gerak parabola. Kata-kata kunci: Student’s Conceptual Construction Guider , kesulitan mahasiswa , Gerak Parabola